UMPAN BENUA (UNGKAPAN UCAP SYUKUR MASYARAKAT SINTANG) - Devota, Alodia; Ina, Ina; Suhardi, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractVocabulary is one of the most important parts of learning meaning of vocabulary for second language learners, Chinese. Vocabulary includes morphemes, words, phrases and sentences. In linguistic phenomena, some morphemes and word have similar meaning. For example "diu" and "shi". From the classification of Chinese vocabulary, "diu" and "shi" are not the same concepts, and "diu" belongs to words while "shi" belongs to morphemes. In order to understand the mastery of "diu" and "shi" of mastery condition of Mandarin Education Study Program FKIP UNTAN 2016 students, the writer used a test method to examine students understanding and difficulties of the alphabet "diu" and "shi". The results of the study stated that the mastery of students in the alphabet "diu" was better than "shi". The correct rate of "diu" is 65%, while the correct rate of "shi" is only 54%. The writer finds the students haven't totally mastery of "diu" to indicate shelf; put down (idioms), (trends) and have the meaning of leaving and letting go; put down (trends) and "shi" to indicate "uncontrolled" meaning, can be limited to: (yi+shi~) and express with other morphemes to form a fixed case.Keywords: Alphabet, Diu and shi, Condition of Mastery